2004
DOI: 10.1111/j.1467-9701.2004.00597.x
|View full text |Cite
|
Sign up to set email alerts
|

Financing the Provision of Global Public Goods

Abstract: Bradford Scholars -how to deposit your paper Overview Copyright check• Check if your publisher allows submission to a repository.• Use the Sherpa RoMEO database if you are not sure about your publisher's position or email openaccess@bradford.ac.uk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
31
0
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 31 publications
0
31
0
2
Order By: Relevance
“…conferring purely public benefits so that free riding amongst donors may be a concern (Anand, 2004;Kanbur, Sandler, & Morrison, 1999). Foreign aid has been estimated as providing a large and growing share (over 40Q of all aid) in the form of public goods to recipient nations (e.g., Ferroni & Mody, 2002;World Bank, 2001).…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…conferring purely public benefits so that free riding amongst donors may be a concern (Anand, 2004;Kanbur, Sandler, & Morrison, 1999). Foreign aid has been estimated as providing a large and growing share (over 40Q of all aid) in the form of public goods to recipient nations (e.g., Ferroni & Mody, 2002;World Bank, 2001).…”
mentioning
confidence: 98%
“…Anand (2004),Kaul, Stern & Grunberg (1999),Kaul et al (2003), andSandler (1997Sandler ( , 2004 cover several issues related to global and regional public goods, ranging from financing considerations to the underlying nature of these public goods.…”
mentioning
confidence: 98%
“…Much of this increase was in terms of NPGs: during 1996-98, 29.40 per cent of official assistance funded NPGs compared with 8.79 per cent for TPGs. Raffer (1999) 4 In a interesting article, Anand (2004) indicated that this third property is, at times, institutionally determined and not necessarily an innate property of the good. This is also true for non-rivalry and non-excludability.…”
Section: Public Good Aidmentioning
confidence: 97%
“…We focus on the group of ecosystem services that are both public and international. These are services that: (i) cover more than one group of countries; (ii) benefit not only a broad spectrum of countries but also a broad spectrum of the global population; (iii) meet the needs of both present and future generations (Kaul et al 1999;Anand 2004). International public goods generated in any one county must therefore generate spillover effects beyond a nation's boundary (Morrissey et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…In most cases, it is not possible for any single state to provide such goods on its own. International public good supply depends on either international coordination or international cooperation (Anand 2004).…”
Section: Introductionmentioning
confidence: 99%